Tuberculosis Verucossa Cutis of Hand: A Case Report - Prathyusha M; Amila Sainudheen; Sandra Puthean (Nepal Journal of Dermatology, Venereology & Leprology)
Tuberculosis verrucosa cutis (TBVC) is exogenous paucibacillary cutaneous tuberculosis (CTB) and is the third commonest type of CTB. Clinically, TBVC usually begins as isolated or multiple warty papules, and soon acquires a verrucous plaque and are usually located in the extremities. Here we report a case of 41-year-old South Indian woman presenting with occasional pruritus, erythematous scaly nodules and warty plaques on the back of right hand following nail prick. A positive Mantoux test, skin biopsy showing granuloma and related epidemiologic, clinical and histopathologic data with an excellent response of patient to the treatment confirmed TBVC.